HUBUNGAN KARAKTERISTIK DAN PERILAKU IBU HAMIL DALAM PEMENUHAN KEBUTUHAN GIZI DENGAN KEJADIAN KEKURANGAN ENERGI KRONIS (KEK) - Rani Darma Sakti Tanjung; Nani Jahriani (Jurnal Maternitas Kebidanan, 2022)
Pregnant women need to provide adequate nutrition for the fetus. However, there are still many pregnant women who still prioritize the nutrition of their families rather than themselve. This study aims to determine the relationship between maternal behavior in meeting nutritional needs and the incidence of chronic energy deficiency (KEK) in pregnant women.This research is an analytic study with a cross sectional design. The study was conducted in the working area of ​​the Sigambal Health Center, Rantau Selatan District, Labuhanbatu Regency in January 2022. The population in this study was 221 people, and 36 people were taken which were divided into 18 case groups and 18 control groups. Data were analyzed by univariate and bivariate using Chi-Square test with 95% confidence level (a = 0.05). Showed that the variables related to the incidence of Chronic Energy Deficiency (KEK) in the work area of ​​the Sigambal Health Center, Rantau Selatan District, Labuhanbatu Regency, namely parity (p = 0.035), pregnancy distance (p = 0.018), knowledge (p = 0.041), attitude ( p=0.035), and action (p=0.18). The unrelated variable was age (p=0.140) income (p=1,000). It is recommended to the leadership of the Sigambal Health Center, Rantau Selatan District, Labuhanbatu Regency to instruct health workers, especially village midwives to provide nutritional counseling or counseling to pregnant women in their work areas so that the behavior of pregnant women in meeting nutritional needs becomes good and mothers do not experience Chronic Energy Deficiency. (SEZ).